EMOTIONAL INTELLIGENCE TRAINING FOR TEACHERS: IMPACTS ON CLASSROOM CLIMATE AND STUDENT BEHAVIOR - Baso Intang Sappaile; Ahmad Amir Aziz; Restianingsih Putri Rahayu (Adisam Publisher, 2026)
This study aims to analyze the effect of emotional intelligence training for teachers on classroom climate and student behavior through a literature review approach. Emotional intelligence is one of the important competencies that teachers must possess in facing the increasingly complex dynamics of modern learning. Teachers who have the ability to manage emotions, build empathy, and create positive communication tend to be able to create a conducive learning atmosphere and support the social and academic development of students. The research method used is a literature review by examining various scientific articles, national and international journals, academic books, and previous research results relevant to the topic of emotional intelligence training, classroom climate, and student behavior. Data were analyzed descriptively and comparatively to identify patterns, relationships, and key findings from the various sources reviewed. The results show that emotional intelligence training has a positive impact on teachers' abilities to manage stress, increase empathy, strengthen interpersonal communication, and build more harmonious relationships with students. In addition, the application of emotional intelligence in learning can create a more positive classroom climate, increase student participation, reduce levels of conflict and aggressive behavior, and encourage the formation of disciplined and collaborative behavior in students. Thus, emotional intelligence training for teachers plays a strategic role in creating a healthy, inclusive learning environment that supports the sustainable development of student character.